Interpersonal interaction between the teacher and the future specialist of water transport - Скляренко, Інна Юріївна (Pedagogy of Higher and Secondary Education, 2017)
The article is devoted to the analysis of interpersonal interaction between teachers and future specialists of water transport in conditions of professional pedagogical activity in the team. In the course of the research, the analysis of the scientific literature and generalization of the results of the developments on the existing problems, consultation with competent persons and purposeful observation of the life activity of the really functioning student groups are used. The article shows the relationship between the existing types of teachers and the nature of interpersonal interaction with future specialists in water transport. It is noted that the cumulative nature of interpersonal relationships in the «teacher-student» depends on the types described by teachers and is subjective. Thus, if the teacher dominated authoritarian style building interpersonal relations, future professionals of water transport manifests status anxiety, uncertainty, anxiety, and, dissatisfaction, irritability, aggressiveness sometimes explicit – a condition that is inherently educational manifestation of stress. The organization of the educational process in the form of a dialogue as a type of interpersonal communication is especially important when the teacher being the person alone forms the personality of the future specialist water transport, its outlook, which guarantees its continuous professional growth and development of life, values. However, in practice teachers, despite many positive changes in ducation in recent years, the prevailing traditional approach to the educational process. The importance of the teacher’s authority in the process of interpersonal interaction is argued. Found that teacher awareness of the activity leads to the creation of human relationships that create a culture of communication of teachers and students in terms of interpersonal interaction. This communication forms the personality of the future specialist water transport his personal position, outlook, attitude, which guarantees its continuous professional growth and development of life and values. It is established that the prospects for further research lie in the study of various aspects of interaction between the teacher and the future specialist of water transport.